Stalagmite multi-proxy records of weak Asian summer monsoon interval during Termination III as an analogue to Termination I - Chen, Gongzhe (2023)
Multi-proxy analysis of abrupt climate change during Ice Age Termination III (T-III) is necessary to understand Asian summer monsoon (ASM) characteristics and mechanisms. We present 230Th dates and δ18O, δ13C, with equilibrium diameter, carbonate deposition amount and lithological characteristics from an annually laminated stalagmite (No. YXB) in Yongxing Cave, central China. Our multi-proxy records span 243.90 to 239.20 ka before present, falling within T-III/Marine Isotope Stage 7e. The changes in δ18O, equilibrium diameter, carbonate deposition amount, and lithological characteristics suggest a weak ASM interval during T III. By comparing these results with records from Ice Age Termination I (T-I), we find that the weakened ASM event during T-III is similar to the Younger Dryas (YD) event in terms of duration and structure. This result suggests that the YD-like event could be an inherent feature of glacial-interglacial climate cycles in the middle and late Pleistocene. The YXB δ13C sequence, without YD-like events, is broadly similar to the δ18O record on orbital timescale, indicating that variations in local vegetation could be driven by rising CO2 during ice age terminations.